Defining priority issues for managing stray dog populations: The case of Greece - Papavasili, TE; Kontogeorgos, A; Mayrommati, A; Chatzitheodoridis, F; Sossidou, EN (Journal of the Hellenic Veterinary Medical Society, 2023)
Recent literature on stray dogs offers evidence about their increasing overpopulation. However, very few studies have attempted to investigate and explain the overpopulation of stray dogs in Greece. The aim of this study is to define how different social and professional groups prioritize issues related to management practices and programs that could be adopted at national and regional level. The Delphi method was applied for drawing, experiences, information, knowledge and opinions of fourteen experts serving from different professions and positions the topic of the study in order to demonstrate how the participation and cooperation of all stakeholders will lead to a sustainable management of their population. The process was completed in three rounds of online meetings in which participants were asked to fulfill questionnaires to analyze their choices. It was concluded that stray dogs are overpopulated mainly due to the "irresponsible ownership of the pet dog" which usually leads to its abandonment (most often without neutering), and the uncontrolled reproduction of stray dogs. Also, the lack of interest in adopting stray dogs was a matter of high priority. Finally, neutering strays and pets was demonstrated by the majority of experts as a solution against overpopulation of stray dogs